Location Specificity and the Transferability of Downstream Assets to Foreign Subsidiaries - Anand, Jaideep; Delios, Andrew (Journal of international business studies, 1997)
We investigate the effect of firm-specific advantages being 'local' in scope, and the influence of subsequent location-specific disadvantages, on the choice of foreign entry mode and subsidiary performance. To look into this issue, we examine Japanese FDI data from the wholesale and retail industries - two sectors that have productive activity concentrated in downstream processes and location-bound resources. Our theoretical and empirical analyses demonstrate that, in situations where required capabilities must be developed through local experience and where location-specific resources were subject to market failure, acquisition and joint venture strategies were preferred. Greenfield entries were successful in industries that permitted the off-setting of location-specific disadvantages with firm-specific advantages. From our results, we draw implications for the entry mode literature and offer a perspective on the performance of the entry mode choice.